RESPON TANAMAN JAGUNG TERHADAP DOSIS ABU CANGKANG KELAPA SAWIT PADA TANAH ULTISOL - Hutauruk, Sixtus; Zega, Apkris Volman (AGROSUSTAIN, 2023)
This study aims to determine the response of corn plants to doses of oil palm shell ash on Ultisol soil. This study used a non-factorial Randomized Block Design (RBD) with the treatment being a dose of palm shell ash (A), which consisted of 7 levels, namely: A0 = 0 g/polybag (Control), A1 = 15 g/polybag, A2 = 30 g/polybag, A3 = 45 g/polybag, A4 = 60 g/polybag, A5 = 75 g/polybag, A6 = 90 g/polybag. Parameters observed were plant height, number of leaves, stem diameter, leaf area, cob length without cob, cob diameter without cob, cob weight with husk, cob weight without cob, and strawweight. Based on the results of the study it can be stated that the higher the dose of oil palm shell ash, it will be followed by the increase in plant height, leaf area, stem diameter, leaf area, cob length without cob, cob diameter without cob, cob weight with cob, cob weight without cob. and strawweight.